Synthesis routes of zeolitic imidazolate framework-8 for CO2 capture: A review - Singh A.; Vedrtnam A.; Kalauni K.; Singh A.; Wdowin M. (My University, 2025)
Zeolitic imidazole framework-8 (ZIF-8) represents a notable subtype of metal-organic frameworks (MOFs), characterized by tetrahedral and zeolite-like structures interconnected through Imidazolate anions. ZIF-8’s outstanding attributes, including its expansive intra-crystalline surface area and robust chemical and thermal stability, have positioned it as a promising contender for carbon dioxide (CO2) capture applications. The application of ZIF-8 in the membrane and composite fields involves utilizing ZIF-8 in the development and enhancement of membranes and composite materials for gas separation, catalysis, and sensing. This article serves as a comprehensive exploration of contemporary CO2 capture technologies, elucidating their respective merits and demerits. Moreover, the review offers insights into the prevailing CO2 adsorption techniques implemented across industries. Delving into ZIF-8 synthesis methods, the discourse encompasses diverse synthetic pathways. Experimental evidence, furnished through X-Ray diffraction patterns and scanning electron microscopy, validates ZIF-8’s structure-activity correlation and morphological characteristics. We extend this review to encapsulate the parameters governing CO2 adsorption by ZIF-8, delineating the key factors influencing its capture efficacy. Notably, we encompass CO2 measurement protocols and techniques specific to ZIF-8. Additionally, we appraise the CO2 adsorption potential of ZIF-8 within various composite and filter systems composed of distinct ZIFs. Culminating with an emphasis on ZIF-8’s exceptional advantages for CO2 capture, this review serves as a repository of insights into the unparalleled potential of ZIF-8 as a foundational material. Providing a succinct yet comprehensive overview, this article facilitates a rapid understanding of ZIF-8’s transformative role in the realm of C2 capture. © 2025 the Author(s), licensee AIMS Press. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0)